Folic acid supplementation for sow diets - Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Folic acid is an essential B-vitamin for swine, and green, leafy plants are an -excellent source of this vitamin. Even though pigs cannot synthesize folic acid, bacteria in their lower gut can, making feces another source of folic acid. Research in the late 1940's and early 1950's indicated that folic acid supplementation to pig diets was not necessary. However, in the last 40 years, the number of sows raised in outside lots with access to leafy plants has decreased. Also, improvements in waste removal systems have decreased the sow's access to fecal material. These changes in management systems have removed two sources of folic acid from the sow, thereby, causing researchers to reevaluate folic acid supplementation to sow diets.
Keywords: Swine; Flic acid; Sow diets